2016
DOI: 10.1016/j.exer.2016.04.015
|View full text |Cite
|
Sign up to set email alerts
|

A model of progressive photo-oxidative degeneration and inflammation in the pigmented C57BL/6J mouse retina

Abstract: Light-induced degeneration in rodent retinas is an established model for of retinal degeneration, including the roles of oxidative stress and neuroinflammatory activity. In these models, photoreceptor death is elicited via photo-oxidative stress, and is exacerbated by recruitment of subretinal macrophages and activation of immune pathways including complement propagation. Existing light damage models have relied heavily on albino rodents, and mostly using acute light stimuli. These albino models have proven va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
89
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 59 publications
(97 citation statements)
references
References 45 publications
(57 reference statements)
7
89
0
1
Order By: Relevance
“…Perhaps LD-dependent complement expression is different in murine and rat retina. This hypothesis is supported by novel data of the same group showing, that for pigmented light treated mice c3 mRNA expression decreases after a peak expression at d5 again in contrast to c3 expression in rats (Rutar et al, 2011; Natoli et al, 2016)…”
Section: Discussionmentioning
confidence: 55%
“…Perhaps LD-dependent complement expression is different in murine and rat retina. This hypothesis is supported by novel data of the same group showing, that for pigmented light treated mice c3 mRNA expression decreases after a peak expression at d5 again in contrast to c3 expression in rats (Rutar et al, 2011; Natoli et al, 2016)…”
Section: Discussionmentioning
confidence: 55%
“…Although there is no clear direct evidence that light causes irreparable retinal degradation over a human being’s lifetime, it is widely believed that oxidative stress and activation of the immune system caused by long-term exposure to moderate light, in addition to ageing (i.e. metabolic and circulatory changes, and immune-senescence) can lead to progressive tissue damage in the retina (Natoli et al 2016; Organisciak et al 1998; Penn and Anderson 1987; Rutar et al 2011, 2012; Youssef et al 2011). Retina’s prior light-experience (so-called ‘light history’) has been shown to be essential for determining its sensitivity to subsequent acute light damage, suggesting that retinal cells may acclimate to their environment thereby maximizing their ability to survive on the long-term (Organisciak et al 1998; Penn and Anderson 1991).…”
Section: Introductionmentioning
confidence: 99%
“…1 Previous studies have shown that b-alanine treatment administered in the drinking water at a concentration of 3% causes a decline in taurine plasma levels [34][35][36] and in tissues such as the hippocampus, posterior cortex, and retina, as well as in cellular taurine content 13,14,[37][38][39][40] and also that taurine depletion causes loss of retinal neurons 6,41-43 (see below). [50][51][52] Light is a risk factor for some retinal degenerations, [53][54][55][56] and it accelerates photoreceptor degeneration in some inherited retinal degenerations. 54,[57][58][59] In previous work, [18][19][20]50 we documented that light exposure causes rapid photoreceptor degeneration and, longterm, alterations in all the retinal layers and RGC loss.…”
Section: Discussionmentioning
confidence: 99%